Progressive Coronary Dilatation Predicts Worse Outcome in Kawasaki Disease - Chih, Wan-Ling; Wu, Pei-Yuan; Sun, Li-Chuang; Lin, Ming-Tai; Wang, Jou-Kou; Wu, Mei-Hwan (The Journal of pediatrics, 2016)
To explore the implication of serial coronary changes on the late coronary outcomes in patients with Kawasaki disease (KD) with coronary aneurysms ≧4 mm. We performed a retrospective review of 78 patients with KD with large coronary aneurysms (1980-2013, male: 76.9%; 792 patient-years). Progressive coronary dilatation was defined for those with progressive enlargement of coronary arteries in 3 consecutive echocardiograms. We studied 27 patients with KD with giant aneurysms (≧8 mm) and 51 patients with KD with medium aneurysms (4-8 mm). All the giant and 43.1% of medium aneurysms persisted during the study period. For the patients with giant aneurysms, their 10-year freedom from acute myocardial infarction/cardiovascular death and all ischemia was 66% and 52%, respectively. The median intervals for the aneurysm diameters reaching their peak were 3.3 months (giant) and 0.25 months (medium), respectively. In patients with giant aneurysms, the 10-year freedom from ischemia was much lower in those with progressive coronary dilatation (28% vs 59%, P = .021). In patients with medium aneurysms, the probability of 5-year persistence of aneurysm was much greater (67.2% vs 14.8%, P < 10−3) in those with progressive coronary dilatation. Male sex and intravenous immunoglobulin therapy were not associated with the late outcomes in the patients with KD who had aneurysms larger than 4 mm. In addition to coronary diameters 1 month after the onset of KD, progressive coronary dilatation at 2 or more months after diagnosis may be an indicator of duration, and the severity of vasculitis and adverse dilative remodeling were associated with worse late coronary outcomes.